"It Is Not the End of Parenting": Extended Parenthood and Child Launching Experiences Among Middle-Aged Korean American Mothers. Issue 3 (June 2022) - You, Soo-Bin; Nesteruk, Olena
This study explored how middle-aged Korean American mothers perceive their children's transition to adulthood and make sense of their changing parenting experience. Guided by a phenomenological approach, the analysis of semi-structured interviews with first-generation Korean immigrant mothers ( N = 10) of young adult children revealed their culturally unique perceptions of children's independence and parenting approach during child launching. Specifically, to the mothers, the current child launching period meant extended parenthood until a child's marriage which was viewed as the completion of full launching. While welcoming their children's independence and autonomy, they believed that their children still needed parental support due to prolonged education and financial instability. These mothers actively engaged in their children's decision-making process representing their reluctance to fully allow their children's autonomy and felt ambivalent with the uncertainty of their children's independence. The study findings have implications for providing Korean immigrant families with useful assistance and support in practical settings.